PETROLOGY AND GEOCHEMISTRY OF DORE VOLCANISM SORONG, WEST PAPUA - YUNIARNI - NIM: 22015035, RUM
Dore Volcanic rocks is well exposed in Sorong, Bird Heads of Papua. This volcanic forms as basaltic lava and andesitic lava. Petrographicly, the basalt possesses a special texture that is glomerophorphyritic pyroxene and sieve pyroxene - sieve plagioclase. The andesite-andesite basaltic rock is also characterized by a special texture that is sieve plagioclase. The characterized by glomerophorphyritic pyroxene and sieve pyroxene sieve-plagioclase indicates a magma mixing process had occurred. In general, the Dore Volcanic rocks had altered into prophylitic alteration as shown by the presence of secondary mineral such as epidote and chlorite. In this volcanic rocks, there are two periods of alteration in which the secondary minerals is cut by calcite vein. The un-continuous distribution on major element composition pattern as shown on Na2O, K2O and TiO2 elements is interpreted to be an original characteristic of different magma source in which basalt (SiO2=45.50% - 50.39%) and andesite (SiO2=53.34 – 55.8%) are non comagmatic. The basalt with MgO content ranges from >6.11 to 13.32% indicated a primitive magma, and the low content of TiO2 (<1.25%) is belong to a tholeiitic magma. Andesite – basaltic andesite have MgO content <6,00%, a calk-alkaline affinities with TiO2 content <1.25% that indicate the magma is related to subduction process.The Rare Earth Element diagram normalizing into chondrite shows that the andesite and basalt have different magma source. The basalt graphic pattern trend tend to be flat from HFSE to LFSE/LILE and it is similar to MORB pattern with TiO2 content <1.25%. This flat pattern of the basalt is typical of the magma that occurred within the Back Arc Basin Basalt (BABB) or marginal basin basalt environment. The graphic pattern of andesite lava is relatively enriched or going up from HFSE to LFSE/LILE which indicated it related to subduction process. The Dore Volcanic rocks evidence shows that magma mixing had occurred more than two periods. Based on the magma fractionation – differentiation the evolution of magma is that primitive magma of basalt-1– basalt-2– andesite within the tectonic subduction – Back arc Basin environments and continental enrichment. On the basis of petrological data from Arfak–Yapen–Dore the age of Eocene–Miocene volcanism in the Bird Head and Yapen have basalt–andesite composition with tholeiite to calk-alkaline affinitites. The geochemical characteristic of the Dore Volcanic is thought to be influenced by the magma mixing which was caused by the tectonic process. The present day position of Eocene–Miocene volcanic rocks in the Bird Head–Yapen resulting by the tectonic emplacement. During tectonic process had resulted difference volcanic rock composition in the three areas (Arfak-Yapen-Dore). The Volcanic Dore is more low alkaline and more primitive than the rests.